Synthesis and Characterization of New Palladium(II) Thiosemicarbazone Complexes and Their Cytotoxic Activity against Various Human Tumor Cell Lines - Hernández Gorritti, Wilfredo Román (2013)
Corrección del artículo (29 de marzo de 2015): https://doi.org/10.1155/2015/915270